Taxing Financial Transactions : An Assessment of Administrative Feasibility - Brondolo, John (IMF Working Papers; Working Paper, 2011)
This paper considers how a tax on financial transactions could be applied to three broad and partially overlapping categories of financial instruments: (1) exchange-traded instruments; (2) over-the-counter instruments; and, (3) foreign exchange instruments. For each category, the paper examines the factors that would facilitate or complicate the administration of a financial transactions tax, the options for collecting the tax, the types of compliance risks that are likely to be encountered, and measures for mitigating these risks.